Methotrexate-Induced Lung Involvement in Psoriasis Patients: A single Centre Cross-Sectional Study - Naseemullah, Farooq Azam Khan, Syed Bilal Ahmed, Ayesha Samad Dogar, Amber Afshan, Khalid Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Methotrexate is used for psoriasis as first-line disease-modifying drugs however it may cause lung complications. Objective: The aim of the current study was to find out the Prevalence of Methotrexate-Induced Lung Involvement in Psoriasis Patients. Methodology: The current cross-sectional study was conducted at the department of dermatology Qazi Hussain Ahmad Medical Complex MTI Nowshera from October 2022 to October 2023 after taking approval from the ethical committee of the institute. A total of 78 individuals with psoriasis who visited the OPD were included. Each individual was receiving systemic methotrexate treatment. Details like age, gender, psoriasis type, and medication history were recorded in the patient files. Descriptive statistics, such as frequency counts and percentages, were used to analyze the data. Results: A total of 78 participants of both genders were examined for psoriasis. Out of 78 individuals 12(16%) had mild to moderate and 5(6.6%) had severe lung involvement and 61(81.33%) had no lung complication. the most common kind of psoriasis examined was plaque psoriasis 65(86.6%) followed by Guttate psoriasis 5(6.6%) and Inverse psoriasis 3(4%) respectively. 57(73.0%) of the participants were receiving methotrexate treatment, whereas 43(55.1%)were receiving cyclosporine treatment, 14(17.9%) were receiving acitretin treatment, and 5(6.4%) we’re receiving phototherapy treatment. Of the patients, 35 (44.8%) had been taking methotrexate for less than five years, and 35 (44.8%) had been taking it for 6-10 years Conclusion: The results of the study reveal that while methotrexate-induced lung involvement is a potential adverse effect of long-term psoriasis treatment. 81.33% of the study’s participants showed no signs of lung involvement. More research is necessary to determine whether long-term methotrexate use increases the risk of lung involvement in patients with psoriasis. Keywords: Prevalence; Methotrexate; Lung Involvement; Psoriasis